Is Reform in Accounting Education Needed in China and Russia: A Literature Review - Theodore T. Y. Chen (Australasian Accounting, Business and Finance Journal, 2015)
The purpose of this study is to examine, through literature review, whether China and Russia are in need of accounting education reforms when they are not English-speaking, do not have developed accounting systems as major English-speaking countries do, have a different political orientation from the selected English-speaking countries and are at a transition stage from a state-planned economy to a market-driven economy. The paper is based entirely on literature review of global forces at play on accounting education reform, accounting education change in selected English-speaking countries and developments in accounting education in Russia and China. The review indicates that the two countries have a desperate need for accounting education change and that gradual changes are taking place in both countries, although China is at a more advanced stage of development because of its international trade. There are signs of both countries leaning towards the direction of the Accounting Education Change Commission’s (AECC) initiatives. China is focusing more on breadth of education than specialization and Russia is at a preliminary stage having to enhance its financial reporting system. The available literature on accounting education in Russia and China is limited, particularly in Russia as the Soviet’s old system did not offer accounting degrees. However, this does not present a problem in identifying an accounting education trend in these two countries from the available literature as explained in the final section of this paper “Limitations of This Study and Future Research”. With major English-speaking and non English-speaking countries leaning towards AECC in their accounting education reforms regardless of the political orientation of the country, one may conclude that AECC is the direction that developing countries having the same need for change should consider. The comparison made in this paper provides insights into an area that received little or no attention in the past.
Keywords: Accounting Education; Literature review; Reform; China; Russia